Oxidation of Isodrimeninol with PCC Yields Drimane Derivatives with Activity against Candida Yeast by Inhibition of Lanosterol 14-Alpha Demethylase - Victor Marin; Andres Iturra; Andres Opazo; Bernd Schmidt; Matthias Heydenreich; Leandro Ortiz; Verónica A. Jiménez; Cristian Paz (Biomolecules, 2020)
Candida species cause an opportunistic yeast infection called Candidiasis, which is responsible for more than 50,000 deaths every year around the world. Effective treatments against candidiasis caused by non-albicans Candida species such as C. glabrata, C. parapsilosis, C. aureus, and C. krusei are limited due to severe resistance to conventional antifungal drugs. Natural drimane sesquiterpenoids have shown promising antifungal properties against Candida yeast and have emerged as valuable candidates for developing new candidiasis therapies. In this work, we isolated isodrimeninol (C1) from barks of Drimys winteri and used it as starting material for the hemi-synthesis of four sesquiterpenoids by oxidation with pyridinium chlorochromate (PCC). The structure of the products (C2, C3, C4, and C5) was elucidated by 1D and 2D NMR spectroscopy resulting in C4 being a novel compound. Antifungal activity assays against C. albicans, C. glabrata, and C. krusei revealed that C4 exhibited an increased activity (IC50 of 75 μg/mL) compared to C1 (IC50 of 125 μg/mL) in all yeast strains. The antifungal activity of C1 and C4 was rationalized in terms of their capability to inhibit lanosterol 14-alpha demethylase using molecular docking, molecular dynamics simulations, and MM/GBSA binding free energy calculations. In silico analysis revealed that C1 and C4 bind to the outermost region of the catalytic site of 14-alpha demethylase and block the entrance of lanosterol (LAN) to the catalytic pocket. Binding free energy estimates suggested that C4 forms a more stable complex with the enzyme than C1, in agreement with the experimental evidence. Based on this new approach it is possible to design new drimane-type sesquiterpenoids for the control of Candida species as inhibitors of 14-alpha demethylase.